Guide simplifie de demande d’acces pour les utilisateurs des ressources génétiques regit par le Protocole de Nagoya et celles regit par le Traite International des Ressources Phytogenetiques pour l’Alimentation et l’Agriculture a Madagascar - Andriamahazo, M.; Rakotoniaina, M. (2018)
These guidelines introduce the legal instruments and systems established in Madagascar for the mutually supportive implementation of the International Treaty and the Nagoya Protocol, describing the public bodies involved in the administration of these laws. The guidelines also include how to steps for access seekers applying for access to plant genetic resources in Benin, including forms and templates to be completed when submitting requests. Very significantly, these guidelines were co-developed by the two lead agencies responsible for the administration of the International Treaty and the Nagoya Protocol respectively.